10(8m+9)=10(6m-3)

Simple and best practice solution for 10(8m+9)=10(6m-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(8m+9)=10(6m-3) equation:


Simplifying
10(8m + 9) = 10(6m + -3)

Reorder the terms:
10(9 + 8m) = 10(6m + -3)
(9 * 10 + 8m * 10) = 10(6m + -3)
(90 + 80m) = 10(6m + -3)

Reorder the terms:
90 + 80m = 10(-3 + 6m)
90 + 80m = (-3 * 10 + 6m * 10)
90 + 80m = (-30 + 60m)

Solving
90 + 80m = -30 + 60m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-60m' to each side of the equation.
90 + 80m + -60m = -30 + 60m + -60m

Combine like terms: 80m + -60m = 20m
90 + 20m = -30 + 60m + -60m

Combine like terms: 60m + -60m = 0
90 + 20m = -30 + 0
90 + 20m = -30

Add '-90' to each side of the equation.
90 + -90 + 20m = -30 + -90

Combine like terms: 90 + -90 = 0
0 + 20m = -30 + -90
20m = -30 + -90

Combine like terms: -30 + -90 = -120
20m = -120

Divide each side by '20'.
m = -6

Simplifying
m = -6

See similar equations:

| 8x+-8y=5 | | X-366=415 | | -5x+9=2x-4 | | x+3x+54+2x=180 | | 8p-8=8(-6p-8) | | 2x-6x+4=-12 | | 6x^2-8x-11=0 | | 4m^2-36m= | | x(3x+54)(2x)=180 | | 31=9t-13t+7 | | 19-13p=17p-8 | | (-3n+5)(-5.7)= | | 1.5+.3(h-6)=.8h+2 | | -[6x-(3x+5)]=-4-[4(2x-4)-3x] | | 37+3n=-2 | | (5y-4)(6y-7)= | | 5+2k=3k-3 | | (-8x^4+6x+3)+(2x^4-2x^2+7)= | | 10X^4-6X^3+8X^2=0 | | 22j+11=4j-7 | | q=1000+25p+q | | 6+1(8x+12)= | | X-366=314 | | 90=n+n-10 | | 11x-5-6x=6x-2 | | 2x+y=10x+90 | | x(3x+54)(2x)=360 | | -8+6x=2x+16 | | X=4x-3x-10 | | -30+-80= | | 11x-(2x-5)=32 | | 10x+4=12x-15 |

Equations solver categories